Characterization of Lactic Acid Bacteria Isolated From the Gastrointestinal Tract of a Wild Boar as Potential Probiotics - Li, Miao; Wang, Yi; Cui, Hongyu; Li, Yongfeng; Sun, Yuan; Qiu, Hua-Ji (Frontiers in Veterinary Science, 2020)
Lactic acid bacteria (LAB) are major microorganisms used for probiotic purposes and prime parts of the human and mammalian gut microbiota, which exert important health-promoting effects on the host. The present study aimed to evaluate and compare the probiotic potential and safety of LAB strains isolated from the gastrointestinal tract of a wild boar from the Greater Khingan Mountains, China. Amongst all of the isolated LAB strains, five isolates identified as Lactobacillus mucosae, Lactobacillus salivarius, Enterococcus hirae, Enterococcus durans, and Enterococcus faecium, were remarkably resistant to acid and bile salt. The probiotic characteristics (including adhesion capability, antimicrobial activities, autoaggregation, and coaggregation abilities), and safety properties (including hemolytic activity, antibiotic resistance, absence/presence of virulence factors, and in vivo safety) were evaluated. The results showed that all five isolates exhibited high adhesive potential, remarkable aggregation capacity, and antibacterial activities. Upon assessment of the safety, these strains were negative for hemolytic activity and all tested virulence genes. In vivo safety assessment showed no adverse effects of isolated strains supplementation on the body weight gain and organ indices of the treated mice. This study revealed that these LAB isolates, especially L. salivarius M2-71, possess desirable probiotic properties and have great potentials for the development of feed additives for animals to promote health.